PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KOMITMEN ORGANISASI PADA RUMAH TAHANAN NEGARA KELAS II B PONOROGO - Galuh Cahyaning Putri (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
The purpose of this study was to describe the effect of transformational leadership on organizational commitment in class IIB Ponorogo state prison. The methodology used is focused on quantitative methods by distributing questionnaires to employees of the Class II B Ponorogo State Detention Center as primary consideration. Leadership is something that must be owned by someone and gives influence by someone to their organization. There is one leadership style, namely transformational which influences the organization at the Class II B State Detention Center in Ponorogo. As a measure of Transformational leadership variables using the Multifactor Leadership Questionnaire (MLQ) and Organizational Commitment Questionnaire (OCQ), this measure is used to obtain detailed results. As a reference in assessing the application of transformational leadership style, the data sample is all employees of the State Detention Center with a total of 62 respondents. After carrying out the research, it was concluded that there is a strong relationship between transformational leadership and organizational commitment.